A Macaw (Ara sp.) in a Preceramic Site from the Sabana de Bogotá, Colombia, Dated to the Ninth Millennium cal BP. Issue 1 (March 2021) - Zorro-Luján, Catalina M.; Grouard, Sandrine; Noè, Leslie F.; Lefèvre, Christine; Zazzo, Antoine; Langebaek-Rueda, Carl; Peña, Germán; Correal-Urrego, Gonzalo
Abstract : The attribution of osteological remains of a bird discovered in Preceramic deposits at Nemocón IV rockshelter (Sabana de Bogotá, Colombia) to Ara sp. (macaws) is confirmed through osteological and morphometrical analyses. Thirteen bones were recovered from two adjacent, arbitrary excavation levels; and are considered the remains of a single individual because of the rarity of the taxon, their similar size and taphonomic alteration, and the presence of paired elements. Radiocarbon dating of the macaw reveals it comes from the ninth millennium cal BP, the oldest date recorded from Nemocón IV. Paleoenvironmental data suggest that, during the deposition of the Preceramic levels at Nemocón IV, climatic conditions were close to those of today. The modern range of the macaws is outside these climatic parameters, and all modern Ara species are allochthonous to the Sabana de Bogotá, indicating the archaeological macaw was also allochthonous in Preceramic times. Analysis of the remains shows the macaw was not dismembered, so it is unlikely that it was used as food. Early conquest records indicate macaws were traded and maintained outside their natural ranges as pets, as a source of feathers, for use in rituals, or for a combination of uses.